2020
DOI: 10.1177/1744806920911536
|View full text |Cite
|
Sign up to set email alerts
|

Bone cancer-induced pain is associated with glutamate signalling in peripheral sensory neurons

Abstract: We previously identified that several cancer cell lines known to induce nociception in mouse models release glutamate in vitro. Although the mechanisms of glutamatergic signalling have been characterized primarily in the central nervous system, its importance in the peripheral nervous system has been recognized in various pathologies, including cancer pain. We therefore investigated the effect of glutamate on intracellular electrophysiological characteristics of peripheral sensory neurons in an immunocompetent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Glutamatergic signaling has also been shown to play a critical role in the peripheral sensitization and mechanical hypersensitivity associated with CIBP. Zhu et al (2020) showed that glutamate injection-induced neuronal excitation in dorsal root ganglia (DRG) is similar to that shown to be induced by CIBP. In a breast cancer model of CIBP, sulfasalazine reduced nociceptive perception and delayed onset of behavioral pain signs ( Ungard et al, 2014 ; Ellingson and Vanderah, 2020 ; Zhu et al, 2020 ).…”
Section: Glutamate Receptorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Glutamatergic signaling has also been shown to play a critical role in the peripheral sensitization and mechanical hypersensitivity associated with CIBP. Zhu et al (2020) showed that glutamate injection-induced neuronal excitation in dorsal root ganglia (DRG) is similar to that shown to be induced by CIBP. In a breast cancer model of CIBP, sulfasalazine reduced nociceptive perception and delayed onset of behavioral pain signs ( Ungard et al, 2014 ; Ellingson and Vanderah, 2020 ; Zhu et al, 2020 ).…”
Section: Glutamate Receptorsmentioning
confidence: 86%
“… Zhu et al (2020) showed that glutamate injection-induced neuronal excitation in dorsal root ganglia (DRG) is similar to that shown to be induced by CIBP. In a breast cancer model of CIBP, sulfasalazine reduced nociceptive perception and delayed onset of behavioral pain signs ( Ungard et al, 2014 ; Ellingson and Vanderah, 2020 ; Zhu et al, 2020 ). Furthermore, in a rat model of CIBP, direct inhibition of NMDAR in the spinal cord led to nociceptive relief ( Dai et al, 2017 ).…”
Section: Glutamate Receptorsmentioning
confidence: 86%
“…Also, recently another study demonstrated the effect of an aberrant system x c by injecting glutamate intramuscularly in the BCP model. They treated the tumor implanted mice with sulfasalazine which modulates system x c and rectified the glutamate signaling leading to relief from pain behavior . This suggests that neurotrophins, their receptors, glutamate, and system x c played an important role in the peripheral sensitization during BCP and may serve as potential targets in the mitigation of the same.…”
Section: Peripheral and Central Mechanisms Encoding Bone Cancer Painmentioning
confidence: 99%
“…To quantify this excitability, the threshold of depolarizing current pulses of 100 ms each, injected with an amplitude of 500 to 4000 pA in 500 pA increments into the soma was determined using the Protocol Editor function in pClamp 9.2. The conduction velocity (CV) was used to categorize DRG sensory neurons as follows: C-fiber neurons �0.8 mm/ms, Aδ-fiber neurons 1.5-6.5 mm/ms, and Aβ-fiber neurons >6.5 mm/ms [41,49]. The threshold of activation, the depth of the receptive field, and the pattern of adaption were the major factors used to further classify neurons into LTM, HTM, and unresponsive neurons [41,[49][50][51].…”
Section: Drg Neuron Excitabilitymentioning
confidence: 99%
“…The conduction velocity (CV) was used to categorize DRG sensory neurons as follows: C-fiber neurons �0.8 mm/ms, Aδ-fiber neurons 1.5-6.5 mm/ms, and Aβ-fiber neurons >6.5 mm/ms [41,49]. The threshold of activation, the depth of the receptive field, and the pattern of adaption were the major factors used to further classify neurons into LTM, HTM, and unresponsive neurons [41,[49][50][51]. HTM neurons responded to noxious stimuli, including a noxious pinch and application of pointed objects such as the sharp end of a syringe needle, whereas LTM neurons responded to innocuous stimuli such as a moving brush, light pressure with a blunt object, a light manual tap, or vibration.…”
Section: Drg Neuron Excitabilitymentioning
confidence: 99%